Heterotrophy of filamentous oleaginous microalgae Tribonema minus for potential production of lipid and palmitoleic acid. (September 2017) - Zhou, Wenjun; Wang, Hui; Chen, Lin; Cheng, Wentao; Liu, Tianzhong
Highlights: Heterotrophic ability of microalgae Tribonema minus was identified for the first time. Glucose and urea were the optimal sources for heterotrophic fermentation of T. minus. Highest biomass and lipid productivity of 30.8 g L −1 and 730 mg L −1 d −1 were obtained. The percentage of palmitoleic acid in fatty acid profile reached up to 50.1%. Effects of nutrient, pH and temperature on T. minus heterotrophy were investigated. Abstract: Heterotrophic fermentation and high valuable co-product producing are thought to be effective ways to improve the economic viability and feasibility of commercial production of microalgae biofuels. This work reported the heterotrophic cultivation of Tribonema minus for lipid and palmitoleic acid (a novel functional fatty acid) production. Firstly, the heterotrophic ability of T. minus was identified for the first time with significant promotion in biomass and lipid productivity, and glucose and urea were then selected as the optimal carbon and nitrogen sources. Moreover, nutrient concentrations and culture conditions were optimized. Highest biomass and lipid productivity of 30.8 g L −1 and 730 mg L −1 d −1 were obtained respectively by adding 80 g L −1 glucose at once. In addition, 2 g L −1 urea, 0.8 g L −1 K2 HPO4, 24 mg L −1 ammonium ferric citrate, initial pH of 6, and temperature of 27 °C were determined as the appropriate conditions for heterotrophic growth and lipid production.